Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.452
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Drinking Norms from Attending Drinking Events and Social Network Site Use

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…It is important to note that previous research found a significant relationship between perceived exposure and perceived injunctive norm of the given behavior ( Zhang and Jemmott, 2014 ; Nesi et al, 2017 ; Rui and Stefanone, 2017 ; Yang and Zhao, 2017 ), which the present study did not replicate. One possible explanation is that those studies focus on questionable behaviors such as alcohol consumption ( Nesi et al, 2017 ; Rui and Stefanone, 2017 ; Yang and Zhao, 2017 ) and sexual encounters ( Zhang and Jemmott, 2014 ). Whether these behaviors are deemed proper is contextual ( Cialdini et al, 1990 ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…It is important to note that previous research found a significant relationship between perceived exposure and perceived injunctive norm of the given behavior ( Zhang and Jemmott, 2014 ; Nesi et al, 2017 ; Rui and Stefanone, 2017 ; Yang and Zhao, 2017 ), which the present study did not replicate. One possible explanation is that those studies focus on questionable behaviors such as alcohol consumption ( Nesi et al, 2017 ; Rui and Stefanone, 2017 ; Yang and Zhao, 2017 ) and sexual encounters ( Zhang and Jemmott, 2014 ). Whether these behaviors are deemed proper is contextual ( Cialdini et al, 1990 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, although research provided a wealth of evidence on the effect of perceived exposure on perceived injunctive norms ( Zhang and Jemmott, 2014 ; Nesi et al, 2017 ; Rui and Stefanone, 2017 ; Yang and Zhao, 2017 ), this direct relationship may not hold in the present study. As explained earlier, research reviewed above focuses on questionable behaviors.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations